Misi dan Dialog dalam Konteks Multikultural dan Pluralitas Agama - Arip Surpi Sitompul; Lilis Manurung; Hotlan Tarida Silaban; Albert Frinando Sitompul (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
Religious and cultural diversity are inseparable realities of modern society. In the era of globalization, interactions among people from different religious and cultural backgrounds have become increasingly intensive, creating both opportunities and challenges for the practice of religious mission. These conditions require an inclusive, contextual, and dialogical approach in order for mission to remain relevant and constructive within pluralistic communities. This study aims to analyze the relationship between mission and dialogue in the context of multiculturalism and religious plurality. The research employs a qualitative method with a library research approach. Data were collected from books, scientific journals, and relevant theological documents, and were analyzed descriptively and interpretively. The findings indicate that mission should not be understood merely as the proclamation of the Gospel, but as active participation in Missio Dei, expressed through acts of love, justice, compassion, and peace. Interreligious dialogue serves as a strategic means of fostering tolerance, mutual understanding, respect, and cooperation among people of different faiths. The integration of mission and dialogue therefore represents a relevant and transformative approach for promoting social harmony and peaceful coexistence in pluralistic societies, particularly in the Indonesian context.